Chronic Cognitive Deficits and Associated Histopathology Following Closed-Head Concussive Injury in Rats - Deng-Bryant, Ying; Leung, Lai Yee; Madathil, Sindhu; Flerlage, Jesse; Yang, Fangzhou; Yang, Weihong; Gilsdorf, Janice; Shear, Deborah (Frontiers in Neurology, 2019)
Close-head concussive injury, as one of the most common forms of traumatic brain injury (TBI), has been shown to induce cognitive deficits that are long lasting. A concussive impact model was previously established in our lab that produces clinically relevant signs of concussion and induced acute pathological changes in rats. To evaluate the long-term effects of repeated concussions in this model, we utilized a comprehensive Morris water maze (MWM) paradigm for cognitive assessments at one and six months following repeated concussions in rats. As such, adult Sprague-Dawley rats received either anesthesia (sham) or repeated concussions (4 consecutive impacts at 1hr interval). At 1 month post-injury, results of the spatial learning task showed that the average latencies to locate the hidden “escape” platform were significantly longer in the concussed rats over the last two days of the MWM testing compared to sham controls (p<0.05). In the memory retention task, rats subjected to repeated concussions also spent significantly less time in the platform zone searching for the missing platform during the probe trial (p<0.05). On the working memory task, the concussed rats showed a trend toward worse performance, but this failed to reach statistical significance compared to sham controls (p=0.07). At 6 months post-injury, no differences were detected between the concussed group and sham controls in either the spatial learning or probe trials. However, rats with repeated concussions exhibited significantly worsened working memory performance compared to sham controls (p<0.05). In addition, histopathological assessments for axonal neurodegeneration using silver stain showed that repeated concussions induced significantly more axonal degeneration in the corpus callosum compared to sham controls (p<0.05) at 1 month post-injury, whereas such difference was not observed at 6 months post-injury. Overall, the results show that repeated concussions in our model produced significant cognitive deficits in both spatial learning abilities and in working memory abilities in a time-dependent fashion that may be indicative of progressive pathology and warrant further investigation.